Cultural institutions in Poland: the nature of their organisation and financing - Gałecka, Małgorzata; Smolny, Katarzyna (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Previous research regarding the external conditions of public cultural institutions inspired us to analyse the internal conditions of individual institutions. Aim: The purpose of the current study is to answer the question of whether and how the internal regulations pertaining to theatres based on financial, organisational, and creative autonomy affect the financial and substantive performance of public cultural institutions. In order to achieve the aim of the study and answer the research question, we analysed cultural institutions in terms of their system. Additionally, the financial and substantive situation of the studied theatres was analysed. Results: The lack of clear process and entity requirements affects the dependence of the performance of public cultural institutions on individual, internal organisational arrangements, suggesting the need to unify these processes through a reform of these institutions. Attention should be paid to the transparency of public spending, organizational culture and effectiveness of public cultural institutions. In the current legal status, the conducted showed a large discrepancy in the results of the theatres studied.